2016
DOI: 10.1155/2016/9409452
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Dexamethasone Exposure Increases the Susceptibility to Autoimmunity in Offspring Rats by Epigenetic Programing of Glucocorticoid Receptor

Abstract: Objective. Prenatal glucocorticoids (GC) can induce long term effects on offspring health. However, reports and related studies regarding the prolonged effects of prenatal GC on the development of autoimmunity are limited. Here, we aimed to explore the immunological effects of dexamethasone (DEX) exposure on young adults and whether glucocorticoid receptor (GR) is involved in this process. Methods. Wistar rats were given DEX during pregnancy. Susceptibility to autoimmunity in offspring was assessed using exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…In mice, the cardiovascular and renal renin-angiotensin-aldosterone systems also respond to elevated prenatal corticosterone in a sexually-dimorphic manner, potentially through altering adrenal function [4547]. Epigenetic factors may also play a key role in the glucocorticoid-driven effects of fetal programming, including altered methylation status of GR following neonatal dexamethasone exposure [48]. It is important to recognize the timing of exposure when considering the correlation between animal models and human fetuses.…”
Section: Glucocorticoids Regulate the Function Of Organs In The Repromentioning
confidence: 99%
“…In mice, the cardiovascular and renal renin-angiotensin-aldosterone systems also respond to elevated prenatal corticosterone in a sexually-dimorphic manner, potentially through altering adrenal function [4547]. Epigenetic factors may also play a key role in the glucocorticoid-driven effects of fetal programming, including altered methylation status of GR following neonatal dexamethasone exposure [48]. It is important to recognize the timing of exposure when considering the correlation between animal models and human fetuses.…”
Section: Glucocorticoids Regulate the Function Of Organs In The Repromentioning
confidence: 99%
“…Obviously, prenatal exposure to glucocorticoids can alter the epigenome of the offspring, affecting multiple organs and pathways ( 75 ). Therefore, in addition to the observed effects on TCR repertoire, we cannot discard epigenetic effects on glucose metabolism or pancreatic beta cell development as disease modifiers ( 76 ), and research on this topic is ongoing. Moreover, changes in the microbiome are likely to influence immune system development in the offspring ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study performed in rats demonstrated that prenatal dexamethasone, another glucocorticoid, exposure increases the susceptibility to autoimmunity, namely, experimental autoimmune encephalomyelitis (EAE) and adjuvant‐induced arthritis (AIA) in offspring (Sun et al, ). The study found that epigenetic programing of the glucocorticoid receptor in peripheral blood mononuclear cells was associated with susceptibility to AIA and EAE (Sun et al, ).…”
Section: Autoimmunitymentioning
confidence: 99%